PENAFSIRAN HUKUM TERHADAP TINDAK PIDANA PENYEBARAN HOAX DALAM PERSPEKTIF HUKUM PIDANA - Zhikrillah Zhikrillah; Erdianto Effendi; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The legal provisions regarding hoaxes are in Act Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions governing the spread of hoaxes for violators may be subject to the following sanctions: Article 45 A paragraph 1, i.e. false and misleading news content, Article 45 A paragraph 2, which is a charge that causes hatred or hostility of certain individuals and / or groups of people based on ethnicity, religion, race, and between groups (SARA). Hoax is also regulated in Article 390 of the Criminal Code, only in terms of trade. Therefore, the formulation of the problem of writing this thesis, namely: first how is the interpretation of the law against the spread of hoax criminal law perspective? Second, can hoax distribution be subject to rules in terrorism laws?This type of research used in this study is normative, in this research the writer chooses a study of legal principles. Sources of data used, namely: primary data, secondary data and tertiary data. Data collection techniques namely the method of library research, as well as this study were analyzed using qualitative analysis.The conclusion that can be obtained from the results of the first research, Referring to Law Number 11 of 2008 concerning Information and Electronic Transactions, hoaxes are more appropriate if Law Number 11 of 2008 concerning Information and Electronic Transactions is applied, because in Law Number 11 of 2008 concerning Information and Hoax electronic transactions are widely regulated. Second, the spread of hoaxes can be subject to terrorism laws if investigators have proven that who is actually the perpetrators of hoaxes, are investigated against the background of the spread of hoaxes to the element of intentions that can make the public feel anxious and afraid, in addition there is a form of psychological intimidation from the spread of hoaxes the perpetrators. So if these elements are fulfilled, then it is concluded, the perpetrators are included as a terrorist network or only as a hoax spreader. However, if hoaxes are not involved in terrorist networks, law enforcement officials cannot apply Law Number 5 of 2018 concerning Eradication of Terrorism Criminal Acts. Suggestions are expected for the future of the Government of Indonesia to provide a broader definition and scope regarding the phrase "terrorism" and the phrase "hoax". And the government must classify a hoax as a criminal offense into several provisions. This is because the material on hoaxes can be diverse and the impact can be very detrimental to the public.Keywords: Legal Interpretation - Criminal Acts – Hoax